2022
DOI: 10.1136/bjsports-2021-104539
|View full text |Cite
|
Sign up to set email alerts
|

Educational online prevention programme (the SPRINT study) has no effect on the number of running-related injuries in recreational runners: a randomised-controlled trial

Abstract: ObjectivesThe aim of this study was to examine the effectiveness of an enhanced online injury prevention programme on the number of running-related injuries (RRIs) in recreational runners.MethodsWe conducted a randomised-controlled trial in runners who registered for running events (distances: 10–42.195 km) in the Netherlands. Adult runners who provided informed consent were randomised into the intervention or control group. Participants in the intervention group received access to the online prevention progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
0
16
0
5
Order By: Relevance
“…Mean age and body mass index ranged between 28 and 43 years and 23.3 kg/m 2 and 33.3 kg/m 2 , respectively. The most common interventions evaluated were running shoe prescription (n=6),33–38 multicomponent exercise therapy (n=4),39–42 variations on a graduated running programme (n=3)43–45 and online injury prevention education programmes (n=3) 46–48. Single trials evaluated the effect of running technique retraining49 and an injury prevention education programme (practical workshop) 50.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mean age and body mass index ranged between 28 and 43 years and 23.3 kg/m 2 and 33.3 kg/m 2 , respectively. The most common interventions evaluated were running shoe prescription (n=6),33–38 multicomponent exercise therapy (n=4),39–42 variations on a graduated running programme (n=3)43–45 and online injury prevention education programmes (n=3) 46–48. Single trials evaluated the effect of running technique retraining49 and an injury prevention education programme (practical workshop) 50.…”
Section: Resultsmentioning
confidence: 99%
“…Single trials evaluated the effect of running technique retraining49 and an injury prevention education programme (practical workshop) 50. Knee injury was diagnosed by participant self-report in 11 studies33–36 40 41 43 45–48 and clinical examination by a medical professional in 7 studies 37–39 42 44 49 50. Running-related injury definition varied between studies (online supplemental appendix 4), and the period of monitoring for injury ranged between 4 weeks and 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prevalent running-related injuries are medial tibial stress syndrome, Achilles tendinopathy, plantar fasciitis, patellar tendinopathy, iliotibial band syndrome, stress fractures of the tibia, and patellofemoral pain syndrome [ 28 , 110 ]. Very recently, a study conducted on more than 4000 runners reported virtually no benefit of a comprehensive prevention program on injury risk [ 111 ]. The implemented program included various pieces of advice pertaining to load progression and management, footwear, subjective aspects, and running-specific exercises.…”
Section: Resistance Exercise For Reducing the Risk Of Running-related...mentioning
confidence: 99%